2020
DOI: 10.1186/s12885-020-07321-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of prior cervical cytology and HR-HPV testing in women subsequently diagnosed with CIN1, CIN2/3, and invasive cervical cancer: a 4-year routine clinical experience after implementation of systematic training and quality control programs

Abstract: Background: In 2013, Jinan KingMed Diagnostics (JKD) first established a systematic cervical cytology training and quality control (QC) program in Shandong Province, China. We compared the efficacy of high-risk human papillomavirus (HR-HPV) detection, cytology, and their combination in routine clinical practice after the implementation of the training and QC program to identify the optimal first-line screening method in this region. Methods: The data of patients histologically diagnosed with cervical intraepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Patients who were diagnosed with suspected AE according to the published AE diagnostic criteria ( 1 , 13 ) in Guizhou Province between June 1, 2020, and June 30, 2021 and who had anti-neuronal antibodies detected by Guizhou KingMed Diagnostics Group Co., Ltd. were included in this study. KingMed is regarded as the pioneer and leader of the Independent Clinical Laboratories (ICL) industry and is the first ICL with both CAP and ISO15189 accreditation in China ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients who were diagnosed with suspected AE according to the published AE diagnostic criteria ( 1 , 13 ) in Guizhou Province between June 1, 2020, and June 30, 2021 and who had anti-neuronal antibodies detected by Guizhou KingMed Diagnostics Group Co., Ltd. were included in this study. KingMed is regarded as the pioneer and leader of the Independent Clinical Laboratories (ICL) industry and is the first ICL with both CAP and ISO15189 accreditation in China ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…21,22 This indicated that the quality of assessment screening cytology in Poland was suboptimal and needed improvement. The highest quality of cytology evaluation may be achieved by ongoing regular training and certification of staff involved in slides evaluation, as proposed by some studies 23 ; other researchers suggested that only the level of slides' difficulty influences the agreement rates rather than staff's academic or professional degrees. 24,25 The occurrence of 24.3% of truly normal slides sampled before CC diagnosis might have resulted from: (1) location of lesions deep in endocervical canal hampering appropriate sampling; (2) improper sampling and (3) true lack of lesions at the moment of sampling and their rapid development and progression.…”
Section: Results Of Fn Auditmentioning
confidence: 99%
“… 21 , 22 This indicated that the quality of assessment screening cytology in Poland was suboptimal and needed improvement. The highest quality of cytology evaluation may be achieved by ongoing regular training and certification of staff involved in slides evaluation, as proposed by some studies 23 ; other researchers suggested that only the level of slides' difficulty influences the agreement rates rather than staff's academic or professional degrees. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that the negative expression of Ki-67 was closely related to the missed diagnosis by MSCT, as an independent risk factor. Probably, the patients with negative Ki-67 expression had lower cell proliferation [24], better prognosis and weaker lymph node metastasis [25]. Moreover, the model established based on the above independent influencing factors had high discrimination, accuracy, and predictive value.…”
Section: Discussionmentioning
confidence: 97%